Atlas of microstructures of constructional materials study aid - Egorov Yu. P. Yuri Petrovich; Strelkova I. L. Irina Leonidovna; Khvorova I. A. Irina Alexandrovna; Baginski A. G. Andrey Gennadievich (Tomsk, Tomsk Polytechnic University Publishing House, 2019)
The atlas of microstructures is a set of photographs of microstructures with descriptions and reference data for study the "Materials Science", the discipline of professional cycle. The Atlas of Microstructures includes such groups of materials as carbon steels, cast iron, non-ferrous metal alloys. The manual is intended for students learning in the direction of 15.03.01 "Mechanical Engineering".